ChemInform Abstract: Synthesis of Pyranocoumarin Fused Spirooxindoles via Knoevenagel/Michael/Cyclization Sequence: A Regioselective Organocatalyzed Multicomponent Reaction. Issue 22 (15th May 2015) - Pal, Suman; Khan, Md. Nasim; Karamthulla, Shaik; Choudhury, Lokman H.
Abstract: The three component reaction of isatins, chromenone (III), and malononitrile in methanol affords the title compounds (IV).